Recent development of plant products with anti-glycation activity: a review - Chinchansure, Ashish A.; Korwar, Arvind M.; Kulkarni, Mahesh J.; Joshi, Swati P. (RSC Advances, 2015)
Diabetes mellitus (DM) is an endocrine disorder characterized by chronic hyperglycemia, which results from an absolute or a relative deficiency of insulin or resistance to insulin. Hyperglycemia is increasingly linked to the pathogenesis of diabetic complications in individuals with long-duration diabetes. One of the inevitable consequences of hyperglycemia is the enhanced accumulation of advanced glycation end-products (AGEs), which are implicated in the pathogenesis of diabetes. Various natural products and their active constituents have reportedly been used for the treatment of diabetes and its complications. Some of these molecules are known to have anti-glycation activity. The search for novel anti-glycation agents from various sources is gaining a lot of importance. Attention has especially been focused on plants with an ethnopharmacological background and also on plants rich in triterpenoids and phenolics, which generally exhibit antioxidant and anti-glycation effects. Plant extracts or compounds obtained from them that possess both antioxidant and anti-glycation activities might have great therapeutic potential for treating diabetic complications. This review highlights the anti-glycation activities of phytochemicals, which will aid in the identification of lead molecules for the development of new anti-glycation drugs.

Rifampicin reduces advanced glycation end products and activates DAF-16 to increase lifespan in Caenorhabditis elegans - Golegaonkar, Sandeep; Tabrez, Syed S.; Pandit, Awadhesh; Sethurathinam, Shalini; Jagadeeshaprasad, Mashanipalya G.; Bansode, Sneha B.; Sampathkumar, Srinivasa-Gopalan; Kulkarni, Mahesh J.; Mukhopadhyay, Arnab (Aging Cell, 2015)
Advanced glycation end products (AGEs) are formed when glucose reacts nonenzymatically with proteins; these modifications are implicated in aging and pathogenesis of many age-related diseases including type II diabetes, atherosclerosis, and neurodegenerative disorders. Thus, pharmaceutical interventions that can reduce AGEs may delay age-onset diseases and extend lifespan. Using LC-MSE, we show that rifampicin (RIF) reduces glycation of important cellular proteins in vivo and consequently increases lifespan in Caenorhabditis elegans by up to 60%. RIF analog rifamycin SV (RSV) possesses similar properties, while rifaximin (RMN) lacks antiglycation activity and therefore fails to affect lifespan positively. The efficacy of RIF and RSV as potent antiglycating agents may be attributed to the presence of a p-dihydroxyl moiety that can potentially undergo spontaneous oxidation to yield highly reactive p-quinone structures, a feature absent in RMN. We also show that supplementing rifampicin late in adulthood is sufficient to increase lifespan. For its effect on longevity, rifampicin requires DAF-18 (nematode PTEN) as well as JNK-1 and activates DAF-16, the FOXO homolog. Interestingly, the drug treatment modulates transcription of a different subset of DAF-16 target genes, those not controlled by the conserved Insulin-IGF-1-like signaling pathway. RIF failed to increase the lifespan of daf-16 null mutant despite reducing glycation, showing thereby that DAF-16 may not directly affect AGE formation. Together, our data suggest that the dual ability to reduce glycation in vivo and activate prolongevity processes through DAF-16 makes RIF and RSV effective lifespan-extending interventions.
Keywords: advanced glycation end products; aging; Caenorhabditis elegans; DAF-16; Glycation; lifespan; rifampicin

Revisiting amino acids and peptides as anti-glycation agents - Chilukuri, H.; Kulkarni, Mahesh J.; Fernandes, M. (Medchemcomm, 2018)
The importance of controlling or preventing protein glycation cannot be overstated and is of prime importance in the treatment of diabetes and associated complications including Alzheimer's disease, cataracts, atherosclerosis, kidney aliments among others. In this respect, simple molecules such as amino acids and peptides hold much promise both in terms of ease and scale-up of synthesis as well as in relation to negligible/low associated toxicity. In view of this, a comprehensive account of literature reports is presented, that documents the anti-glycation activity of natural and non-natural amino acids and peptides. This review also discusses the chemical reactions involved in glycation and the formation of advanced glycation end-products (AGEs) and possible/probable intervention sites and mechanism of action of the reported amino acids/peptides. This aspect of amino acids/peptides adds to their growing importance in medicinal and therapeutic applications.